2011
DOI: 10.1097/qad.0b013e32834be088
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation predicts changes in high-density lipoprotein particles and apolipoprotein A1 following initiation of antiretroviral therapy

Abstract: Background The effects of HIV infection and antiretroviral therapy (ART) on usual lipid levels have been reported. The effects of initiating versus deferring ART on high- and low-density lipoprotein particle concentrations (HDL-P and LDL-P) and apolipoprotein (Apo) levels are not well described. Methods In a subgroup of participants not taking ART at study entry who were randomized in the Strategies for Management of Antiretroviral Therapy (SMART) to immediately initiate ART (‘VS group’) or to defer it (‘DC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…A consistent role of apo B or LDL-P in this grouping is not evident because of the number of outcomes in which both parameters were not statistically significant; however, in instances in which both were significant, both were generally affected to the same extent (35)(36)(37)(38)(39).…”
Section: Association With Plasma Lipids and Lipoproteinsmentioning
confidence: 95%
“…A consistent role of apo B or LDL-P in this grouping is not evident because of the number of outcomes in which both parameters were not statistically significant; however, in instances in which both were significant, both were generally affected to the same extent (35)(36)(37)(38)(39).…”
Section: Association With Plasma Lipids and Lipoproteinsmentioning
confidence: 95%
“…The association between HIV infection and low HDL is well established [29,30]. A recent study [31] suggested that HIV-associated dyslipidemia was, partially at least, related to chronic inflammation, and that the effect of HAART on HDL changes could be mediated by suppressing inflammation. In fact, inflammation induces major changes in HDL levels and composition.…”
Section: Discussionmentioning
confidence: 99%
“…For example, growth, which is an important and often sensitive measure of successful treatment in children and youth, were comparable between PTI and cARTarms, and more recently we have reported no difference between cART and PTI arms in neurodevelopmental test scores performed cross-sectionally in the PENTA 11 children after the end of the trial [10]. Similarly, although a decline in total, low and high-density lipoprotein from baseline was seen in the first 12 weeks off ART among PTI children in the main trial [8], no differences in fasting lipids were observed between the two arms during longterm follow-up; in contrast, PTI was associated with increased low high-density lipoprotein levels in SMART [28].…”
Section: Univariable Analysesmentioning
confidence: 97%